Basic approaches to the diagnosis and therapy of post-traumatic stress disorder - A. V. Vasileva; T. A. Karavaeva; E. P. Lukoshkina; D. S. Radionov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
Based on a review of domestic and foreign literature, the article highlights the main approaches to the diagnosis and treatment of post-traumatic stress disorder (PTSD). The importance of rapid detection and timely provision of medical care for this disease is shown. The definition of PTSD is formulated, the etiological factors are described, the place in modern classifications, clinical features, the main groups of characteristic symptoms. The role of a medical psychologist in a multiprofessional team providing assistance to patients with PTSD is shown. Comprehensive treatment of PTSD should include psychopharmacotherapy, the first line of which are SSRIs, and psychotherapy methods that have scientifically proven effectiveness in relation to this nosology.